2002
DOI: 10.1152/ajpendo.00489.2001
|View full text |Cite
|
Sign up to set email alerts
|

Central leptin increases insulin sensitivity in streptozotocin-induced diabetic rats

Abstract: White. Central leptin increases insulin sensitivity in streptozotocin-induced diabetic rats. Am J Physiol Endocrinol Metab 282: E1084-E1091, 2002; 10.1152/ajpendo.00489.2001.-This study examined the effect of intracerebroventricular leptin on insulin sensitivity in streptozotocin (STZ)-induced diabetic rats. Male Wistar rats were cannulated in the lateral ventricle and, after recovery, administered either intravenous STZ (50 mg/kg) to induce diabetes or citrate buffer. Chronic leptin (10 g/10 l icv) or vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 50 publications
10
85
0
Order By: Relevance
“…In support of this, leptin administration directly into the brain, at doses that have no effect when administered peripherally, normalises blood glucose levels in rodent models of uDM [19][20][21][22]. This glucose-lowering effect of leptin occurs via a mechanism that is independent of reduced food intake, increased urinary glucose loss or recovery of pancreatic beta cells.…”
Section: Leptin Regulation Of Glucose Metabolismmentioning
confidence: 90%
“…In support of this, leptin administration directly into the brain, at doses that have no effect when administered peripherally, normalises blood glucose levels in rodent models of uDM [19][20][21][22]. This glucose-lowering effect of leptin occurs via a mechanism that is independent of reduced food intake, increased urinary glucose loss or recovery of pancreatic beta cells.…”
Section: Leptin Regulation Of Glucose Metabolismmentioning
confidence: 90%
“…The direct effects of leptin on glucose metabolism and insulin signaling have not yet been fully elucidated. However, in vivo studies have shown that leptin improves insulin sensitivity (Ebihara et al, 2001;Lin et al, 2002;Ogawa et al, 1999;Yamauchi et al, 2001) and normalize glucose metabolism in rodents (Chinookoswong et al, 1999;Masuzaki et al, 1999). Transgenic expression of neuron-specific leptin receptor in receptor-deficient mice leads to amelioration of diabetes (de Luca et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…56 The combined effects of the leptin therapy viz increased glucose metabolism and disposal by enhancing GLUT1 and GLUT4 in brown adipose tissue, liver and skeletal muscle asserted by increased leptin signaling along the FAN pathway, together with increased nonshivering thermogenic energy expenditure via EEN as evidenced by enhanced-brown adipose tissue UCP-1 mRNA, seemingly assisted in sustaining euglycemia in these mice. 38,55,56,91,92 Also, hyperleptinemia produced by systemic administration of Ad-lep in three type 1 diabetic rodents resulting from a loss of pancreatic b-cells either inflicted by autoimmune disease as in NOD (non-obese diabetic) mice, or chemically with streptozotocin or alloxan injections, corrected the severe hyperglycemia which was, however, transient paralleling the course of receding hyperleptenimia. 93 The efficacy of circulating leptin was also shown in these paradigms when intravenous infusion of leptin itself for 12 days rapidly impelled normoglycemia with a time course quite similar to that evoked by insulin replacement 94,95 Furthermore, the possibility that restoration of optimal hypothalamic leptin signaling alone imposed euglycemia in these paradigms was verified when leptin supply was endogenously generated solely in the hypothalamus of hyperglycemic streptozotocin-treated mice.…”
Section: Diabetes Typementioning
confidence: 99%
“…2,8,10,15,23,33,34 In this context, recent attention has been devoted to the disclosure that dynamic physiological fluctuations in circulating titers of leptin, a hormone produced primarily by white adipose tissue under the direction of insulin, have a critical role in conferring glucose homeostasis indirectly through the central nervous system. 10,16,[35][36][37][38][39][40][41][42] The goals of this review are to collate major contributions emanating from research conducted with the aid of gene transfer technology in unraveling the neural etiology of this chronic disease of hyperglycemia, which is correctable by leptin gene therapy confined selectively to the hypothalamus, and that this neurotherapy can be gainfully employed to forestall the pathogenesis of diabetes and varied attendant comorbidities.…”
Section: Introductionmentioning
confidence: 99%